An Assessment of Lactobiopolymer-Montmorillonite Composites for Dip Coating Applications on Fresh Strawberries - Bruna-Bugueno, J; Junqueira-Conceicao Goncalve, M (John Wiley and Sons Ltd, 2017)
BACKGROUND: The use of biopolymer coatings appears as a good alternative to preserve highly perishable fruits, as well as the environment. Proteins generally produce films with good mechanical properties, although their highly hydrophilic nature limits the use in many applications. Nanoparticles, such as nanoclays, can play a critical role in improving barrier properties. The present study evaluated the effect of the addition of montmorillonite (MMT)-nanoparticles to a lacto-biopolymer coating, focusing on: (i) the morphological, thermal and barrier properties of the material and (ii) the shelf life of coated fresh strawberries. RESULTS: The addition of MMT improved the water vapor barrier property. Morphological and thermal analysis indicated a good interaction between the milk protein and the nanoclay, which was intercalated within the milk protein base (MPB) matrix, offering a more tortuous path to diffusing migrants. The MMT-MPB coating helped to significantly (P ≤ 0.05) reduce the weight loss, as well as oxygen uptake and the release of carbon dioxide, and improved the fruit firmness and reduced mould and yeast load compared to the uncoated fruits. The addition of MMT gave statistical difference (P ≤ 0.05) in terms of weight loss, subjective global appearance and purchase intention of coated fresh strawberries. CONCLUSION: The addition of nanofillers, such as MMT, into protein-based coating could improve its water vapour barrier and could affect, positively, some parameters of the shelf life of coated strawberries. © 2016 Society of Chemical Industry. © 2016 Society of Chemical Industry